The Relationship Between Self-Concept With Learning Discipline And Student Learning Motivation In Mts Nu Gondanglegi Malang Regency - Fransisca, Arina (Riviera Publishing, 2022)
Positive or negative self-concept in a person can not be separated from the factors that affect the formation and development of self-concept in the student so that they commit various types of violations in school. If the student's self-concept is good then it will also be a student's learning discipline, so this will help students in good learning motivation by maximizing learning time until the fulfillment of the student's goals. The purpose of this research is to find out the relationship between self-concept with learning disciplines and student learning motivation at MTs NU Gondanglegi Malang Regency. This study uses quantitative methods using product-moment correlation analysis techniques. The study sample numbered 77 students. While the way of sampling uses the total sampling sample technique because the population is below 100 subjects. The data collection technique in this study used the Likert scale. The results of the study showed that (1) there is a positive and significant relationship between the self-concept of the study discipline, where r calculates 0.595, while r tables with N = 77 at the level of significance of 5% of 0.220, so r calculates greater than r label (0.695>0.220). So it can be said that a high level of self-concept indicates a high level of student learning discipline. (2) There is a positive and significant relationship between self-concept and learning motivation, where r counts at 0.465, while r tables with N=77 at a significance level of 5% of 0.220, so r counts greater than r label (0.465>0.220). So it can be said that a high level of self-concept indicates a high level of student learning motivation